Sumangêqna Wanuaé: Konstruksi Sosial dan Identitas Lembaga Adat Desa Wanua Tosora di Kabupaten Wajo - Wardana, Ardi (Emik, 2024)
The Village Traditional Institution (LAD) is an institution that carries out traditional functions and is established on the initiative of the village community, which is recognized by the state based on the Regulation of the Minister of Village PDTT RI Number 21 of 2020. LAD Wanua Tosora was formed based on an agreement between the Village Government, the Village Consultative Body, and the community Tosora Village. While most literature related to LAD looks at the role of traditional institutions, this article focuses on the existence of LAD Wanua Tosora in advancing local culture despite facing various challenges.This qualitative research was carried out in Tosora Village, Wajo Regency employing in-depth interview and observation as data collection methods. The informants who participated in this research were 10 people consisting of seven men and three women aged between 24 and 49 years. They are the Tosora Village Head and Trustees, LAD Chair, LAD Members, Chair of the LAD Inauguration Committee, leaders (community, traditional), cultural observers, farmers and village youth, who were recruited purposively.The study shows that the establishment of the Tosora Village Traditional Institution (LAD) faces various challenges, especially regarding the purpose of its formation which is debated between cultural preservation or the potential for new feudalism. The formation of the LAD through community initiatives and an agreement with the village government was formalized by Village Regulation Number 3 of 2022. However, along the way, there was resistance from the community, from the noble descents, and a lack of understanding of local cultural values of the LAD officials. This creates tension and resistance, as well as worsen the relationship between LAD and local communities. Although LAD aims to promote and to preserve culture, its effectiveness is hampered by performance of LAD officials, poor communication, and the insignificant social contribution of LAD officials.